Model of Religious Education for Slow Learner Children in Inclusive Schools in Indonesia - Ru'iya, Sutipyo; Kistoro, Hanif Cahyo Adi; Sutarman, Sutarman; Masduki, Yusron (SCAD Independent, 2023)
School is a formal institution that is the right place for students to develop their potential. National education aims to provide space and educational materials for every student, including slow learner students. Religious education material is one of the materials that must be provided. This research aimed to describe the learning strategies used by religious teachers to slow learning students. This qualitative research used a narrative approach. There were eight participants: Islamic religion teachers, special guidance teachers and two school principals. Data collection through in-depth interviews and analysis with the stages of data reduction, presentation and interpretation. This research found peer teaching and repetition models to be the main learning models. It was consistent with the character of slow-learner students with below-average cognitive abilities. Slow learner students tend to accept material slowly and repeatedly. They were also more comfortable when being taught by peers because, psychologically, they felt the same age. Meanwhile, the biggest obstacle for slow learner students in learning was limited cognitive ability, unstable concentration power and negative image of parents towards children's abilities. The findings of this study are interesting to be used as a reference for teachers and parents in educating slow learner children.